Miejsca pamięci w edukacji obywatelskiej - Majchrzak, Kinga (Studia Edukacyjne, 2019)
The text starts with a short introduction. Then the concept of place is defined and its inherent characteristics are described: its symbolism, multi-sided nature and multidisciplinary connotations. Afterwards the principles of place-based pedagogy are presented and it’s eclectic character is pointed out. Then, attempt explain idea of the memorial sites from the standpoint of history and pedagogy. In the final part the author relates to educational potential of (national) memorial sites and takes a stance on the role of memorial sites in citizenship education.